DOING DRAMA IN ACTION: STUDENTS’ INQUIRY PROCESS INVESTIGATION - Hendi Hidayat; Rina Nursabrina; Sumadi (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
This study was intended to investigate the students’ inquiry process reflected in doing drama activity. The study applied classroom ethnography. The writer spent seven weeks making ethnographic observations and field notes related to doing drama activity, noting what the students do before, during and after the activity. An in depth interview was conducted to 3 participants. The criteria of chosen participants was their performance during the project. They were considered to have more information. The interview aims to know how each phases fit into the overall context of the inquiry process. The findings show that the inquiry process in doing drama activities are reflected in group formation, selection of drama’s title, making synopsis, devision of roles, rehearsal, costume and propery preparation, and drama performance